The interplay of career involvement and goal conflicts: An eight-wave study with STEM professionals - Ruth Noppeney; Aida Alisic; Bettina S. Wiese (Journal of Organizational Behavior, 2022)
Based on a “whole-life”-perspective and integrating theories of self-identity and resource management, the present longitudinal study examines the dynamic relationship between career involvement and conflicts between work and nonwork goals in a sample of 3095 German-speaking doctoral students and doctorate holders (37.0% women) from various STEM fields. We expected increases in goal conflicts to decrease career involvement, and simultaneously tested reciprocal relationships, that is, from involvement on conflicts. The random intercept cross-lagged panel model (RI-CLPM) was used to analyze within-person associations across eight measurement occasions (6-month time intervals) while controlling for between-person effects. At the between-person level, career involvement and goal conflicts were negatively correlated. At the within-person level, results showed negative cross-lagged effects from goal conflicts to career involvement as well as negative cross-lagged effects from career involvement to goal conflicts. This indicates that the interplay of goal conflicts and career involvement can result in either an upward or a downward spiral. Theoretical and practical implications are discussed.
Keywords: 650; career goal conflicts; career involvement; identity; random intercept cross-lagged panel model (RI-CLPM); work and nonwork incompatibilities